Konstruksi Pemasaran Thrifting Menggunakan Media Sosial - Rica Agatha; Cut Salsabila; Nurdiana Holida; Shofia Dwi Nurianti (Universitas Maritim AMNI Semarang, 2023)
This article reviews the existence of social media in thrifting marketing in the lives of teenagers in the era of globalization. This was put into perspective and carried out empirically by Gen z. Consumptive behavior is increasingly occurring and has become a topic that supports people who make thrifting production a public space for their economy. The rise of thrifting in the business economy is a trend that is currently in a significant context. The phenomenological approach explains the general meaning of a number of individuals related to concepts or phenomena that are now becoming popular discussions on social media. There is a driving factor for consumers to buy thrifting goods, namely the social media factor which encourages teenagers to be tempted by models advertised with various products and brands to attract interest. This research discusses the use of qualitative methods in a phenomenological approach. In this research, the research focus is on enthusiasts (consumers) and owners of thrifting to find out how thrifting can give rise to the existence of social media in online thrifting shopping. One measure of consumer satisfaction can be proven by how often they subscribe to the thrifting store. This is in social reality or truth which is assumed to be the result of social construction and the truth of a social reality which has a relative nature.